PRAGMATIC FAILURE IN LISTENING CLASS A CASE STUDY OF X GRADE STUDENTS OF SMK TAMANSISWA CILACAP - Septiyana Pengesti (Jurnal Penelitian Humaniora, 2014)
In communication, sometimes people hear the unrelated utterances between speaker and hearer but the conversation is usually still continued that way. In this way, the pragmatic role is needed. However, in many cases the use of pragmatic might fail for many reasons: cross-culture understanding, or violating the politeness. This case happens not only in real conversation but also the classroom. This article is aimed to analyze the pragmatic failure in listening class of EFL. The discussion starts from the definition of Pragmatics and the speech act, Pragmatic failure and listening skill. It will be followed by the analysis of the pragmatic failure some conversations in listening class of EFL class. This study shows that there are at least five conversations which contain amount of pragmatic failure. The failure produced by the learners is categorized as pragmalinguistic failure related to Tho mas (1983) statement that pragmalinguistic failure related to different branches in linguistics, especially the relation between pragmatics and grammatical forms.